2017
DOI: 10.1016/j.electacta.2017.04.162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Water Structure on the Oxygen Reduction Reaction on platinum electrodes

Abstract: The oxygen reduction reaction (ORR) at different pH values has been studied at platinum single crystal electrodes using the hanging meniscus rotating disk electrode (HMRDE) configuration. The use of NaF/HClO4 mixtures allows investigating the reaction up to pH = 6 in solutions with enough buffering capacity and in the absence of anion specific adsorption. The analysis of the currents shows that the kinetic current density measured at 0.85 V for the Pt(111) electrode follows a volcano curve with the maximum loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
142
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(155 citation statements)
references
References 69 publications
(115 reference statements)
12
142
1
Order By: Relevance
“…As is known, aluminium is oxidized in the anodic direction, oxygen (Equation 3.8) and/or H+ ions (Equation 3.9) are reduced in the cathodic direction. 24 The oxygen reduction is preliminary in the cathodic polarization curves from −0.2 V to −1.35 V vs Ag/AgCl for FeNi mesh. After these values, the sudden increase of the currents shows that the H + is reduced.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…As is known, aluminium is oxidized in the anodic direction, oxygen (Equation 3.8) and/or H+ ions (Equation 3.9) are reduced in the cathodic direction. 24 The oxygen reduction is preliminary in the cathodic polarization curves from −0.2 V to −1.35 V vs Ag/AgCl for FeNi mesh. After these values, the sudden increase of the currents shows that the H + is reduced.…”
Section: Resultsmentioning
confidence: 95%
“…In this interaction, the effect of pH can be shown according to Equation . The studies have shown that as the basicity increases (pH), the oxygen reduction region shifts to the negative …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the mixed mass transfer and charge transfer control of the cathodic reaction rate, the effect of mass transfer on net current density jnet can be theoretically derived by Equation (1) (All the explanation about parameters, variables and constants in the modeling are summarized in Table 1, the same hereinafter): 1jnet=1jct+1jlim where jct is the current density controlled by charge transfer and jlim is the limiting current density controlled by mass transfer. The equation has been widely used in elementary mechanistic models of corrosion [23,24,25]. …”
Section: Modeling Descriptionmentioning
confidence: 99%